Konsep Kebahagiaan Perspektif Thomas Aquinas - Zulkarnaen, Iskandar; Geofani, Ahmad Assidiq (Jurusan Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Adab UIN Sultan Maulana Hasanuddin Banten, 2023)
Happiness is something that is commonly discussed in human life, because all humans definitely have an orientation in their lives, namely happiness. Talking about happiness, Allah SWT is very merciful and most merciful, Allah is so good that he gives various kinds of happiness to humans, namely spiritual and worldly happiness. that the happiness experienced and felt thanks to the body which is decided by the will and reason is still limited and does not bring true happiness. The focus of this research tries to compare Thomas Aquinas' views with the views of other figures regarding happiness. This research uses the type of library research. The data collection technique used is qualitative which tends to use analysis. Is the collection of data or materials related to the discussion themes and problems. The results of this research are that a comparison of views on happiness, one of which is the ancient Greek philosopher Epicurus, considers happiness as the achievement of pleasure and freedom from suffering. For Epicurus, happiness lies in living simply and free from unlimited desires, but in contrast to the view of Thomas Aquinas, he believes that true happiness does not only lie in physical pleasure, but also includes the spiritual dimension and relationship with God. For Thomas Aquinas, true happiness is eternal and lasting happiness.